Nutrient Composition of Pearl Millet Varieties of Rajasthan - Sharma, Shashi; Bhatnagar, Vibha (Annals of Arid Zone, 2016)
Evaluation of nine high yielding pearl millet hyhrid~ or composites along with a local variety of Nagaur district; for proximate principles. namely. nude protein. crude fibre. ash. crude fibre. carbohydrates and energy ,contents. and minerals- namely. calcium and iron contents. revealed that the varieties differed significantly with respect to all the characters. Though none of the high yielding varieties exceeded the local in all the components,the varieties namely ICTP-8203 MP-179). RHB-30. MP-171. WC-C7S and HHB-67 were superior than the local check with respect to proximate principles. Among the varieties. MP-171. MP-254. WC-C75. ICTP-8203 and MH-179 were also superior in mineral contents. Excepting fal with carhohydrate content and ash with calcium content. rest of the characters were either positively correlatcd or the correlation coefficient was nonsignificant. suggesting a possibility of their simultaneous improvement. Since a wide variability for, quality trails has bel~n reported to exist in germplasm. there is scope f,ll' development of varieties with better nutritional quality.